Psychometric analysis of the scales of validity, anancastiness, impulsivity and hypersensitivity of the questionnaire of neurotic disorders - L. I. Tsidik (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The classical test theory, on the basis of which the majority of diagnostic tools was created, has many defects associated with the lack of measuring principles in it. Today, advanced psychometric technologies based on modern test theory are relevant. These include the Rush model. These technologies surpass the classical theory of tests in scientific validity and applied efficiency, created on the basis of their psychometric scales. The purpose of the study: conduct a psychometric analysis of the scales of validity, anancastiness, impulsivity and hypersensitivity, created on the basis of the statements of the questionnaire of neurotic disorders.Surveyed 296 people. The main statistical method of work is the Rush metric system. Results: new scales have been developed: the scales of validity, anancastiness, impulsivity and hypersensitivity based on the questionnaire of neurotic disorders; statements of the presented scales have adequate constructive validity; measures of difficulty points — mainly within the regulatory range from -2 to +2 logites; the scales are one-dimensional, have a relatively balanced metric structure; reliability index validity scale is 0.88, the anancastiness scale — 0,87, the impulsivity scale — 0.82, the hypersensitivity scale — 0,93; scales of anancastiness and impulsivity are able to differentiate 3 levels of severity of properties, and scales of validity and hypersensitivity — 2.